Normal liver chromatin contains a firmly bound and larger protein related to the principal cytosolic target polypeptide of a hepatic carcinogen. - Vinores, S A (1984)
A 14,000-dalton polypeptide was previously reported to be the principal protein target of the carcinogen N-2-fluorenylacetamide (2-acetylaminofluorene) in liver cytosol at the start of hepatocarcinogenesis in rats. The 14,000-dalton polypeptide was purified to homogeneity according to gel electrophoreses in both NaDodSO4-containing medium and acetic acid/urea and also by immunogenicity. An immunologically related form of the cytosolic target polypeptide has now been found to be present in the nuclei of normal rat liver as a 17,500-dalton polypeptide that is firmly and ionically bound to chromatin. Serial salt extractions of isolated liver nuclei or chromatin at 0.15 and 0.35 ionic strengths fail to dissolve the bound polypeptide, according to electrophoretic transfer immunoblot analyses. Most of the 17,500-dalton polypeptide is extracted at 0.65 ionic strength, the remainder at 1.2, and none at 2.0, nor thereafter in 8 M urea. In addition, short-term digestion of purified liver nuclei with micrococcal nuclease solubilizes the 17,500-dalton polypeptide. All three protocols also solubilize low levels of intermediate 17,500- to 14,000-dalton species, the latter size being the same as that of the cytosolic protein target of the carcinogen. The presence of protease inhibitors during the isolations and extractions of the nuclei and chromatin reduces the amounts of these smaller polypeptides. In normal rat liver only nuclei and cytoplasm of hepatocytes contain reactive antigen according to peroxidase-antiperoxidase immunohistochemistry, staining most intensely perilobularly, less in the lobular midzone, and least centrilobularly. The nuclei of the perilobular hepatocytes constitute the strongest staining compartment within all of normal liver. Of 22 nonhepatic tissues of normal rats, 16 contain relatively few cells with immunoreactive cytoplasm. Nonhepatic nuclear antigen is present only in villar crest cells of duodenum (which are normally exposed to liver bile), also having cytoplasmic antigen as well. Five kinds of evidence appear to connect the chromatin-bound 17,500-dalton polypeptide of normal liver nuclei to the cytosolic 14,000-dalton polypeptide that is the principal target of the carcinogen early during hepatocarcinogenesis in rats. The present findings indicate a direct connection between a chromosomal protein and the immediate principal cytosolic protein target of a carcinogen.